Dermatogenic enteropathy. Issue 4 (April 1970) - Marks, Janet; Shuster, Sam
Abstract : Steatorrhoea has been found in a large proportion of patients with inflammatory dermatoses, especially eczema and psoriasis. It is due to the rash itself and disappears rapidly after topical treatment of the skin. This particular enteropathy, unlike that associated with dermatitis herpetiformis, is not accompanied by an alteration in the stereomicroscopic appearance of the small bowel mucosa. The mechanism is not known. It is important to differentiate dermatogenic enteropathy from gluten sensitivity which has produced a rash, as in the former condition a gluten-free diet is not indicated.